The Prevalence and Economic Importance of Bovine Hypodermosis in Ağrı Region, Türkiye - Taşçi, GT; Saltan, C; Aydın, N; Ölmez, N; Yiğit, M; Işık, ME (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, It was aimed to detect the prevalence of hypodermosis, to reveal the role of some epidemiological parameters and to calculate the current economic loss according to hide damage in cattle in Ağrı region of Türkiye. For this purpose, a total of 1857 cattle skin were palpated from 51 farms in 18 locations and 98 cattle were examined postmortemly in slaughterhouses for the presence of Hypoderma spp. larvae between March and May 2023. The breeds, ages, genders and skin colours of animals were recorded. The prevalence of hypodermosis in cattle was found to be 16.85% by skin palpation. The total number of larvae was determined as 3521 on 313 infested cattle. Maximum 46 larvae were counted by palpation on a cattle and the mean larvae count was determined as 11.24. The infestation rates were 10.35% one-year-olds, 26.33% in two-year-olds, 16.80% in three-year and older, while 16.39% in females and 18.02% in males. Infestation rate was higher in native cattle (20.84%) than Brown Swiss crossbred (16.50%) and simmental crossbred (15.89%). In postmortem examination in slaughterhouses, 19 out of 98 cattle were found infested with 69 warble larvae. The economic loss caused by hypodermosis was calculated as 15.780 TL = 553.6 USD (1 USD = 28.5 TL November 2023) in study area.